2006
DOI: 10.1007/s10517-006-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in functional activity of G-proteins hormone-sensitive adenylate cyclase signaling system, during experimental type II diabetes mellitus

Abstract: The development of experimental type II diabetes mellitus in rats was accompanied by dysfunction of inhibitory and stimulatory heterotrimeric G-proteins, components of hormone-sensitive adenylate cyclase signal system. The function of inhibitory G-proteins decreased most significantly under these conditions, which is seen from weakened regulatory effects of somatostatin (in the myocardium) and bromocriptine (in the brain striatum) realized via inhibitory G-proteins in diabetic rats compared to controls. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Kumar et al, 2010). We showed that in the brain of rats with STZ-induced DM1, duration one month, as well as with neonatal model of DM2, duration 3 to 6 months, the sensitivity of AC to regulatory action of bromocriptine was decreased (Shpakov et al, 2006(Shpakov et al, , 2007a. The inhibitory effect of bromocriptine on forskolin-stimulated AC activity and its stimulating effect on GppNHp binding of G i proteins in synaptosomal membranes of diabetic rats were significantly decreased, predominantly in DM1.…”
Section: Dopamine Signalingmentioning
confidence: 99%
“…Kumar et al, 2010). We showed that in the brain of rats with STZ-induced DM1, duration one month, as well as with neonatal model of DM2, duration 3 to 6 months, the sensitivity of AC to regulatory action of bromocriptine was decreased (Shpakov et al, 2006(Shpakov et al, , 2007a. The inhibitory effect of bromocriptine on forskolin-stimulated AC activity and its stimulating effect on GppNHp binding of G i proteins in synaptosomal membranes of diabetic rats were significantly decreased, predominantly in DM1.…”
Section: Dopamine Signalingmentioning
confidence: 99%
“…The MnR projections to ventral striatum are affected by diabetes mellitus more than that of those to dorsal striatum. Study of Shapakov and colleagues showed that the level of serotonin in striatum is not significantly different between diabetic and nondiabetic rats (21). On the other hand, some studies indicate that induction of diabetes mellitus causes a decrease in serotonin level of the striatum (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The peptides corresponding to C-terminal regions 385-394 (α S -subunit) and 346-355 (α i2 -subunit) of human G proteins and polycationic peptides C-εAhx-WKK(C 10 )-KKK(C 10 )-KKKK(C 10 )-YKK(C 10 )-KK (peptide I) and (GRGDSGRKKRRQRRRPPQ) 2 -KεAhx-C(Acm) (peptide II) were synthesized as described previously [1][2][3][4]. eAhx, C 10 , and Acm are the residue of ε-aminohexanoic acid, residue of capric acid, and acetamide group, respectively.…”
Section: Methodsmentioning
confidence: 99%